The Role of Forest Police in Eradicating Bird Hunting in Alas Purwo National Park - Setiawan, Eko (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2023)
This article aims to answer problems related to animal hunting in the Alas Purwo National Park conservation area. An indisputable fact about the richness of biodiversity and ecosystems, but with the rise of poaching can threaten the loss of life of endemic animal species. This research is descriptive qualitative, aiming to provide a systematic and clear picture of the problem of animal hunting. Data collection methods through observation, interviews, and documentation. The source of the data came from key informants, consisting of communities around buffer villages, forestry police, perpetrators of animal thieves, Law Number 5 of 1990 concerning Conservation of Natural and Biological Resources and Their Ecosystems. Data analysis using interactive models, including data reduction, data presentation, drawing conclusions. The results of the study show that the Government's efforts to protect endemic animals are considered less than optimal, even though regulations have been made regarding the prohibition of hunting and trading protected animals. So, it takes the role of the forestry police to act as the spearhead through preemptive, preventive, and repressive security operations. Forest police are at the forefront of combating unlawful acts.